Oxidation of Membrane Curvature-Regulating Phosphatidylethanolamine Lipid Results in Formation of Bilayer and Cubic Structures - Sankhagowit, Shalene (Langmuir, 2016)
Oxidation is associated with conditions related to chronic inflammations and aging. Cubic structures have been observed in the smooth endoplasmic reticulum and mitochondrial membranes of cells under oxidative stress (e.g., tumor cells and virus-infected cells). It has been previously suspected that oxidation can result in the rearrangement of lipids from a fluid lamellar phase to a cubic structure in organelles containing membranes enriched with amphiphiles that have nonzero intrinsic curvature, such as phosphatidylethanolamine (PE) and cardiolipin. This study focuses on the oxidation of 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), a lipid that natively forms an inverted hexagonal phase at physiological conditions. The oxidized samples contain an approximately 3:2 molar ratio of nonoxidized to oxidized DOPE. Optical microscopy images collected during the hydration of this mixture from a dried film suggest that the system evolves into a coexistence of a stable fluid lamellar phase and transient square lattice structures with unit cell sizes of 500–600 nm. Small-angle X-ray scattering of the same lipid mixture yielded a body-centered Im3m cubic phase with the lattice parameter of 14.04 nm. On average, the effective packing parameter of the oxidized DOPE species was estimated to be 0.657 ± 0.069 (standard deviation). This suggests that the oxidation of PE leads to a group of species with inverted molecular intrinsic curvature. Oxidation can create amphiphilic subpopulations that potently impact the integrity of the membrane, since negative Gaussian curvature intrinsic to cubic phases can enable membrane destabilization processes